2015
DOI: 10.1186/s40068-015-0043-0
|View full text |Cite
|
Sign up to set email alerts
|

Change in snow cover area of Brahmaputra river basin and its sensitivity to temperature

Abstract: Background:The discharge of the River Brahmaputra is highly affected by the melting of snow at the upper part of its catchment. Increase in discharge due to significant retreat of snow in turn affects the downstream flow characteristics of the river giving rise to severe catastrophic problems such as flood and erosion. Rising temperature is one of the major reasons of melting of snow at the upper Brahmaputra catchment. Keeping in mind such issue, in this paper, a study has been conducted to see how the snow co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 33 publications
(24 reference statements)
1
5
0
Order By: Relevance
“…Moreover, these results are consistent with the latest study, which has reported based on the MODIS NRT flood product that about 17.7% of the geographical area of North Bihar was inundated during 2020 flood events and the adversely affected districts were Muzzafarpur, Darbhanga, Saharsa, Khagaria, Madhepura, Bhagalpur, Katihar, and Purnea [62]. Previously, during the flood event of August-September 2017, 12% to 17% of the geographical area of North Bihar was inundated during the peak flood period [57]. The composite floods maps over 2000-2020 indicated that about 34% of the area was affected by floods, as derived from the MODIS-based NRT flood product [57].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, these results are consistent with the latest study, which has reported based on the MODIS NRT flood product that about 17.7% of the geographical area of North Bihar was inundated during 2020 flood events and the adversely affected districts were Muzzafarpur, Darbhanga, Saharsa, Khagaria, Madhepura, Bhagalpur, Katihar, and Purnea [62]. Previously, during the flood event of August-September 2017, 12% to 17% of the geographical area of North Bihar was inundated during the peak flood period [57]. The composite floods maps over 2000-2020 indicated that about 34% of the area was affected by floods, as derived from the MODIS-based NRT flood product [57].…”
Section: Discussionsupporting
confidence: 91%
“…The impact of climate change on the water resources of the snow and glacier-dominated river basins is also important for water resource management. The river discharge in the Brahmaputra river is highly influenced by the snowmelt at the upper part of the catchment due to global warming [57]. The snow cover area changes under the recent climatic conditions are expected to have a larger effect on the hydrological cycle [58].…”
Section: Discussionmentioning
confidence: 99%
“…The inverse correlation between SCA and temperature is well established (Bednorz, ; Hosaka et al , ; Gurung et al , ; Maskey et al , ; Barman and Bhattacharjya, ), whereas the spatial variability across elevations is not well understood. Table shows the correlation ( τ ) between the daily average temperature and daily SCA of individual basins during the period between 2000 and 2007.…”
Section: Resultsmentioning
confidence: 99%
“…The 7000m asl elevation marks the transition from negative to positive correlation which has also been reported in Nepal. This pattern may be due to temperatures being well below critical above 7000 m asl, and as a result small changes in temperature do not lead to perceptible changes in SCA (Barman and Bhattacharjya, 2015). The other possible reason could be ablation at higher elevation due to wind erosion and sublimation.…”
Section: Relationship Between Sca and Temperaturementioning
confidence: 99%
See 1 more Smart Citation